Research of Dosimetry Parameters in Small Electron Beams - Nazmiye Donmez Kesen; Aydin Cakir; Murat Okutan; Hatice Bilge (Science and Technology of Nuclear Installations)
In this study, dose distributions and outputs of circular fields with dimensions of 5 cm and smaller, for 6 and 9 MeV nominal energies from the Siemens ONCOR Linac, were measured and compared with data from a treatment planning system using the pencil beam algorithm in electron beam calculations. All dose distribution measurements were performed using the GafChromic EBT film; these measurements were compared with data that were obtained from the Computerized Medical Systems (CMS) XiO treatment planning system (TPS). Output measurements were performed using GafChromic EBT film, an Advanced Markus ion chamber, and thermoluminescent dosimetry (TLD). Although it is used in many clinics, there is not a substantial amount of detailed information in the literature about use of the pencil beam algorithm to model electron beams. Output factors were consistent; differences from the values obtained from the TPS were at maximum. When the dose distributions from the TPS were compared with the measurements from the ion chamber and GafChromic EBT films, it was observed that the results were consistent with 2 cm diameter fields and larger, but the outputs for 1 cm diameter fields and smaller were not consistent.